Is thermal sensitivity affected by predation risk? A case study in tadpoles from ephemeral environments - Miloch, Daniela; Cecchetto, Nicolas R.; Lescano, Julián N.; Leynaud, Gerardo C.; Perotti, María Gabriela (2024)
Fil: Miloch, Daniela. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas, y Naturales. Centro de Zoología Aplicada; Argentina.